Impaired sustained attention in groups at high risk for antisocial personality disorder: A contingent negative variation and standardized low-resolution tomographic analysis study - Guan, Muzhen; Ma, Lifang; Zhu, Yifang; Liao, Yang; Zeng, Lingwei; Wu, Shengjun; Men, Ke; Liu, Xufeng (Frontiers in Human Neuroscience, 2022)
Objective: This study aimed to explore the characteristics of contingent negative variation (CNV) in groups at high risk for antisocial personality disorder. Methods: A classic CNV paradigm was used to compare the characteristics of attention maintenance among a group of individuals with conduct disorder (CD group; n = 27), a group of individuals with antisocial personality traits (AP; n = 29), a group of individuals with conduct disorder and antisocial personality traits (CD + AP group; n = 25), and a group of healthy controls (CG group; n = 30), to examine the characteristics of the amplitude and latency of CNV in different processing stages. Results: Results of the event-related potential analysis were as follows: The mean amplitude analysis between 500-1000 ms revealed that the mean CNV amplitudes in the CD + AP group (-1.388 ± 0.449 μV, P < 0.001) were significantly lower than in the CG group (-4.937 ± 0.409 μV). The mean amplitude analysis between 1000-1500 ms revealed that the mean CNV amplitude in the CD + AP group (-0.931 ± 0.646 μV) was significantly lower than the CG group (4.809 ± 0.589 μV, P < 0.001). The mean amplitude analysis between 1500-2000 ms revealed that the mean CNV amplitude in the CG group (3.121 ± 0.725 μV) was significantly higher than the CD + AP group (-0.277 ± 0.795 μV, P = 0.012), whereas the mean CNV amplitude in the CD + AP group was not significantly different in the AP group (P = 0.168) and CD group (P > 0.05). Source localization results indicated altered activity in frontal-temporal regions. Conclusion: The CNV amplitude characteristics in the CD + AP group and AP group were more consistent and fluctuated around the baseline, indicating the absence of attention maintenance resulted in impairments in attention allocation and motor preparation in the CD + AP group and AP group.